A novel immunogold cryoelectron microscopic approach to investigate the structure of the intracellular and extracellular forms of vaccinia virus. - Roos, N (1996)
We introduce a novel approach for combining immunogold labelling with cryoelectron microscopy of thin vitrified specimens. The method takes advantage of the observation that particles in suspension are concentrated at the air-water interface and remain there during the subsequent immunogold labelling procedure. Subsequently, a thin aqueous film can be formed that is vitrified and observed by cryoelectron microscopy. In our view, a key early step in the assembly of vaccinia virus, the formation of the spherical immature virus, involves the formation of a specialized cisternal domain of the intermediate compartment between the endoplasmic reticulum and the Golgi. Using this novel cryoelectron microscopy approach, we show that in the intracellular mature virus (IMV) the core remains surrounded by a membrane cisterna that comes off the viral core upon treatment with dithiothreitol, exposing an antigen on the surface of the viral core. Complementary protease studies suggest that the IMV may be sealed not by membrane fusion but by a proteinaceous structure that interrupts the outer membrane. We also describe the structure and membrane topology of the second infectious form of vaccinia, the extracellular enveloped virus, and confirm that this form possesses an extra membrane overlying the IMV.